2019
DOI: 10.1136/bmjopen-2018-024439
|View full text |Cite
|
Sign up to set email alerts
|

Reduced long-term care cost by social participation among older Japanese adults: a prospective follow-up study in JAGES

Abstract: ObjectivesReducing costs related to functional disabilities and long-term care (LTC) is necessary in ageing societies. We evaluated the differences in the cumulative cost of public LTC insurance (LTCI) services by social participation.DesignProspective observational study.SettingOur baseline survey was conducted in March 2006 among people aged 65 or older who were not eligible for public LTCI benefits and were selected using a complete enumeration in Tokoname City, Japan. We followed up with their LTC services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
5
26
0
Order By: Relevance
“…The results of the present study support previous studies, but these studies evaluated only one outcome (the need for LTC or death)8–16 and did not take both outcomes into account in a single model 14. The present study is the first to focus on the combination of two relevant outcomes in the same model.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of the present study support previous studies, but these studies evaluated only one outcome (the need for LTC or death)8–16 and did not take both outcomes into account in a single model 14. The present study is the first to focus on the combination of two relevant outcomes in the same model.…”
Section: Discussionsupporting
confidence: 86%
“…It was defined by WHO as a component of the social determinant of health and it contains various kinds of forms as follows: informing people with balanced, objective information; consulting, whereby the affected community provides feedback; involving or working directly with communities; collaborating by partnering with affected communities in each aspect of the decision-making process, including the development of alternatives and the identification of solutions and empowering people by ensuring that communities retain ultimate control over the key decisions that affect their well-being 7. Previous studies have shown that social participation among older people is associated with a reduced risk of the need for long-term care (LTC)8–11 or death 12–16. However, previous studies have several limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These group activities lead to reduced disability incidence and further long-term care costs in older adults. 13,14) Therefore, both the Japanese central and local governments have been promoting community group activities in each community. As a result, the number of groups increased from 43,154 in 2013 to 91,059 in 2017 ( Fig.…”
Section: Not Certifiedmentioning
confidence: 99%
“…A meta-analytic review suggests that the influence of social isolation on mortality is comparable with well-established risk factors like cigarette smoking and alcohol consumption [14]. Being socially isolated also results in higher spending in health and social care services [15,16]. Social isolation is not only prevalent and significant for older adults, but it also affects younger individuals at different stages of life [17][18][19].…”
Section: Introductionmentioning
confidence: 99%